Caracterización de la gestión del conocimiento en las PYMES de "servicios de alimentos y bebidas" del cantón La Maná, año 2020. - Carrillo Cabrera, María José (2022)
The present investigation had as general objective to characterize the knowledge management in the SMEs of food and beverage services "of the La Maná canton, year 2020, due to the fact that in these establishments it was possible to appreciate deficiencies in the knowledge management that was developed empirically. In addition, the owners, due to their inexperience and limited level of education, did not pay due attention to the development of knowledge and skills, and the communication system remained centralized with a degree of distrust on the part of the management personnel when transmitting information. Through a diagnosis of the general and specific characteristics of this type of management, the process of generation, capture, organization, storage, distribution and application of knowledge was subsequently described. Consequently, the deficiencies presented by these micro-enterprises were identified for the establishment of suggestions that generate changes in this sector. For this purpose, bibliographic, field, exploratory and descriptive research was used. While the methods used were inductive and analytical. The application of a census to the 77 owners and surveys to the collaborators was also essential, being necessary for this the calculation of the sample using the statistical sampling formula, giving an amount of 154 people. The results obtained in the field work allowed us to know relevant characteristics of this economic sector that reflected deficiencies: most of them have a service manual, a manual for dealing with suppliers, they do not have flowcharts of the operational processes, they do not have manuals or recipes on the preparation and other operational processes and finally in the stage of application of knowledge difficulties were observed with respect to the knowledge and handling of foreign languages. As a proposal against the shortcomings detected, the knowledge management model based on the principles of Nonaka and Takeuchi was proposed, which contemplated strategies of socialization, Socialization, externalization, combination and internalization, which, when applied, benefited the owners and collaborators of the Food and beverage service SMEs.